OP23 Vascular endothelial growth factor activation of liver sinusoidal endothelial cells via vascular endothelial growth factor receptor-2 regulates hepatocellular hepatitis C virus replication. (16th November 2010) - Rowe, I; Lalor, P; Adams, D; Balfe, P; McKeating, J
Abstract : Introduction: Hepatitis C virus (HCV) is a major concern for human health, with an estimated 180 million people infected worldwide. HCV primarily infects hepatocytes in the liver and the majority of infected subjects develop progressive liver disease. Treatment options remain limited and hence, there is an urgent need for new therapies that target viral and host cell pathways. Vascular endothelial growth factor (VEGF) is a multifunctional cytokine that is produced by a variety of cell types in response to low oxygen and viral infections. VEGF targets vascular endothelial cells that are present in many tissues, including liver sinusoidal endothelial cells (LSEC). LSEC are in close apposition to hepatocytes in the liver and VEGF is known to regulate LSEC proliferation and function. Aim: We recently demonstrated that HCV promotes VEGF expression in hepatocytes (Mee et al, 2010 Gastroenterology ) and the aim of this study was to investigate the role of VEGF in LSEC-hepatocyte interactions in HCV infection. Method: Using primary human LSEC we established direct LSEC-hepatocyte co-culture models to recapitulate the hepatic microenvironment. The effects of VEGF on LSEC and hepatocytes were analysed in both monoculture and co-culture. Results: Initial studies demonstrated that LSEC do not express the full complement of HCV receptors or entry factors and fail to support HCV replication. However, in vitro co-culture of LSEC and hepatocytes to model the hepatic epithelial-endothelial cell environment demonstrated that LSEC significantly reduce the permissivity of hepatocytes to support HCV replication. Interestingly, this effect was abrogated by inclusion of a neutralising antibody or a drug antagonist targeting VEGF receptor-2 (VEGFR-2). Importantly, recombinant VEGF had no effect on HCV replication in hepatocyte monocultures, suggesting that VEGF stimulates endothelial cells to modulate expression of molecules that regulate hepatocyte permissivity to HCV infection. Indeed, conditioned media from VEGF treated LSEC significantly reduced the ability of hepatoma cells to support HCV replication, demonstrating that LSEC modulate expression of a soluble factor that reduces HCV infectivity in response to activation via VEGFR-2. Conclusion: In summary, these data demonstrate a new role for VEGF in endothelial-epithelial cell interactions in the liver that regulate HCV replication and highlight new areas for therapeutic intervention in chronic hepatitis C and other liver diseases.